INTEGRATION BETWEEN RELIGION AND SCIENCE IN EARLY CHILDHOOD EDUCATION LEARNING - Muliza Rahayu (Ta'dib: Jurnal Pendidikan Islam, 2015)
This research is based on research library research literature in this study wanted to try integrate between Religion and Science in learning, there are three questions; first, circumstances of integration between Religion and Science, a description of the example Integration of Religion and Science form the Moon and the theme of nature and explanation in the Qur'an. With analysis and normative content of the Qur'an explain the phenomena of nature with science and science context. Soon is the first research results, the integration of science with nature is a necessity and it is becoming important in the development of sciences as theology that include common knowledge.